Interrupted time series analysis of the impact of DIP reform on hospitalization costs in different types of hospitals - Chun-Hong, Yan; Ke-Xin, Lin; Xin-Yue, Zheng; Xue-Hui, Meng (Frontiers in Public Health, 2025)
ObjectiveIn the context of medical insurance payment reform, this study aims to evaluate the impact of the Diagnosis-Intervention Packet (DIP) payment policy on hospitalization costs across different types and levels of hospitals. In order to provide empirical evidence to support the high-quality collaboration between hospitals and medical insurance, while reducing the economic burden on patients.MethodOur study collected medical insurance reimbursement data from January 2019 to December 2022 in S city, covering 2,467,746 patients. Based on the intervention time point of the DIP reform implementation in 2021, an interrupted time series analysis was conducted on a monthly basis to compare the trend changes in hospitalization costs between traditional Chinese medicine hospitals (TCMHs) and general hospitals (GHs), as well as to examine the differences in impacts across hospitals of various levels.ResultsFirstly, our study found that tertiary hospitals had the highest average hospitalization costs (YTCMH3=6170.33,YGH3=12181.32), followed by secondary hospitals (YTCMH2=4617.47,YGH2=5344.60), and primary hospitals, which had the lowest costs (YTCMH1=2490.93,YGH1=1916.57). Secondly, after the implementation of the DIP reform, the average hospitalization costs immediately decreased in both TCMHs and GHs, with a more significant reduction observed in GHs (β2−TCMH= − 0.023, p = 0.059, β2−GH= − 0.016, p = 0.039). Thirdly, when further categorized by hospital level, we found that the instantaneous effect of the reform on average hospitalization costs was most significant in primary TCMHs (β2−TCMH1= − 0.080, p = 0.008), followed by tertiary TCMHs (β2−TCMH3= − 0.033, p = 0.012), while the effect in secondary TCMHs was not significant (β2−TCMH2= − 0.024, p = 0.087). In GHs, the most significant instantaneous effect was observed in tertiary hospitals (β2−GH3= − 0.046, p = 0.004), while no significant changes were observed in secondary and primary hospitals (β2−GH2= − 0.026, p = 0.077, β2−GH1= − 0.022, p = 0.201). In terms of the long-term effects of the DIP reform, both TCMHs and GHs showed significant changes in average hospitalization costs, with a larger reduction observed in GHs, indicating better reform outcomes (β3−TCMH= − 0.006, p < 0.001, β3−GH= − 0.010, p < 0.001).ConclusionThe government should adjust policies in a differentiated and refined manner based on the type and level of hospitals to achieve the goals of controlling medical costs and improving the incentive mechanisms. Meanwhile, optimizing the healthcare service structure can improve quality and efficiency, as well as better meet patient needs.